MANAJEMEN KNOWLEDGE BERORIENTASI HASIL - Hartiningsih Hartiningsih (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Nowadays the importance of knowledge in order to attain organizational competitive advantage has become major attention. Management scholars regard knowledge and the ability to create and utilize knowledge as the most important source of organizational sustainable competitive advantage. Many of management literatures and school discuss what knowledge management should be and large companies are eager to take advantage of their employees knowledge to organization future growth. Unfortunately, focus of knowledge management effort are on the process of knowledge management it self, not on the goal of the organization or the goal of the knowledge management process. The purpose of this paper is to re-focus of knowledge management effort to the output driven knowledge management.